2007
DOI: 10.1007/s00540-007-0509-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bicarbonate and base excess values analyzed by four different blood gas analyzers

Abstract: Comparison of the calculation formula, reproducibility, correlation and variation of bicarbonate ion concentration (HCO(3) (-)), and base excess value (BE) among four blood-gas analyzers was performed. No HCO(3) (-) and BE values calculated from the formulas showed any clinically significant difference, and all analyzers showed good correlation on their measurements. On the actual measurement of a specific sample, however, BE values from the same sample ranged between -6.3 and -15.7, which might affect therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…1983). Arterial variables measured were pH, partial pressure of oxygen (PaO 2 ), partial pressure of carbon dioxide (PaCO 2 ), bicarbonate (HCO 3 − ) and base excess (BE) (Nakamaru et al. 2007).…”
Section: Methodsmentioning
confidence: 99%
“…1983). Arterial variables measured were pH, partial pressure of oxygen (PaO 2 ), partial pressure of carbon dioxide (PaCO 2 ), bicarbonate (HCO 3 − ) and base excess (BE) (Nakamaru et al. 2007).…”
Section: Methodsmentioning
confidence: 99%
“…We used a quality-controlled commercial blood gas analyzer. It has been shown that different blood gas analyzers provide good reproducibility and correlation for standard bicarbonate, whereas the estimation of BE depends on the algorithm of estimation and type of analyzer [14] [15]. Finally, but not least in importance, we did not consider the powerful role of chloride anions.…”
Section: Discussionmentioning
confidence: 99%